The Labour Market: A Mismatch in the Clothing and Textile Industry in Mauritius (Global Journal of Management and Business Research, 2016)
Abstract not found
Keywords: labour market; clothing and textile industry; mauritius; unemployment; EPZ; apparel industry; labour force; mismatch; labour shortage